Repair of Acute Type-A Aortic Dissection in the Present Era: Outcomes and Controversies - Moeller, Ellie; Nores, Marcos; Stamou, Sotiris C. (AORTA, 2019)
Acute Type-A aortic dissection (AAAD) remains a surgical emergency with a relatively high operative mortality despite advances in medical and surgical management over the past three decades. In spite of the severity of disease, there is a paucity of studies reviewing key controversies surrounding AAAD repair and management. A systematic literature search was performed using Cochrane review and PubMed bibliography review. Abstracts were first reviewed for general pertinence and then articles were reviewed in full. Literature review indicates that use of moderate hypothermia and antegrade cerebral perfusion is a safe alternative to deep hypothermia. In hemodynamically stable patients, axillary cannulation may be substituted for femoral cannulation. With regard to the technical aspects of repair, preserving the aortic root whenever possible and performing the distal anastomosis with the open distal technique rather than with the clamp on is the preferred approach. In patients with a patent false lumen, close monitoring is indicated. As demonstrated by the literature, significant improvement of early and late mortality over the past years has occurred in patients presenting with AAAD. Repair of acute Type-A aortic dissection remains a challenge with high operative mortality; however, improvement of surgical techniques and management have resulted in improvement of early and late clinical outcomes.
Keywords: aortic dissection; outcomes; circulatory arrest; pathophysiology; adults